A Diagnostically Challenging Case of De Novo Febrile Ulceronecrotic Mucha-Habermann Disease with Fatal Pulmonary Involvement: A Case Report - Waseem Alhawsawi; Khalid Al Hawsawi; Bashaer Almahdi; Shahad Alkidaiwi; Khlood Alzubaidy; Reema Alhuthayli; Abdulmohsin Algethami; Alshareef Alshareef (Karger Publishers, 2023)
The febrile ulceronecrotic Mucha-Habermann disease is a rare and potentially lethal variant of pityriasis lichenoides et varioliformis acuta (PLEVA). It is characterized by a sudden onset of ulceronecrotic skin lesions associated with high fever and systemic symptoms. Herein, we report a 23-year-old male, not known to have any medical illnesses, presented with a month-long history of persistent fever of unknown origin associated with a sudden onset of progressive diffuse necrotic ulcers and widespread papulosquamous lesions. Pan CT showed enlarged lymph nodes in the cervix, chest, and abdomen. Unfortunately, a skin biopsy was done late, showing features consistent with PLEVA. Few days after admission, despite being on intravenous methylprednisolone, our patient rapidly deteriorated by showing severe acute respiratory symptoms and consequently died. In spite of the continuous addition of new case reports to the literature, no definite diagnostic criteria have been established, leading to late or missed cases, and an optimum treatment is still waiting.